Altered Circulating Leptin, hGH, and IGF-I in Prediabetes and Screening-Diagnosed T2DM Unrelated to Metabolic Syndrome in Women Post Gestational Diabetes - Kern-Matschilles, Stefanie; Gar, Christina; Schilbach, Katharina; Haschka, Stefanie Julia; Rauch, Barbara; Then, Cornelia; Seissler, Jochen; Bidlingmaier, Martin; Lechner, Andreas (Hormone and Metabolic Research, 2022)
Recently, we proposed two pathophysiologic subtypes of type 2 diabetes mellitus (T2DM), one related and one unrelated to metabolic syndrome. To begin to understand the pathophysiology of the subtype unrelated to metabolic syndrome, we now measured selected hormones and signaling molecules in affected individuals. In this cross-sectional analysis, we examined 138 women out of the monocenter, post gestational diabetes study PPSDiab. Of these women, 73 had prediabetes or screening-diagnosed T2DM, 40 related to metabolic syndrome and 33 unrelated. The remaining 65 women were normoglycemic controls. Our analysis included medical history, anthropometrics, oral glucose tolerance testing, laboratory chemistry, and cardiopulmonary exercise testing. In addition, plasma proinsulin/insulin ratio, growth hormone (hGH) nadir during oral glucose tolerance testing, Insulin-like Growth Factor I (IGF-I), Leptin, Resistin, Adiponectin, Fetuin-a, FGF21, and myostatin were measured. Compared to controls, women with prediabetes or screening-diagnosed T2DM unrelated to metabolic syndrome depicted higher plasma Leptin [10.47(6.6–14.57) vs. 5.52(3.15–10.02); p<0.0001] and IGF-I [193.01(171.00–213.30) vs. 167.97(138.77–200.64); p=0.0008], as well as a lower hGH nadir [0.07(0.05–0.15) vs. 0.14(0.08–0.22; p<0.0001]. These differences were independent of body adiposity. Women with prediabetes or T2DM related to metabolic syndrome, in comparison to controls, displayed elevated Leptin, Fetuin-a, and FGF21, as well as reduced Adiponectin and hGH nadir. Based on our study, altered Leptin and hGH/IGF-I signaling could potentially contribute to the pathophysiology of prediabetes and T2DM unrelated to metabolic syndrome. Further mechanistic investigations of these signaling pathways in the context of lean T2DM are necessary to test causal relationships.
Keywords: insulin resistance; lean risk phenotype; subclassification; insulin secretion